Plasma Induced Graft Polymerization of C6 Fluorocarbons on Cotton Fabrics for Sustainable Finishing Applications. Issue 5 (10th April 2013) - Ramamoorthy, Amsarani; El‐Shafei, Ahmed; Hauser, Peter
Abstract: The main objective of this research is to achieve atmospheric plasma induced graft polymerization of non‐C8 fluorocarbons onto cotton fabrics to achieve a durable nanolayer fluorocarbon coating that is water, alcohol, and oil repellent through home launderings. The influence of process parameters on the performance of polyfluorocarbon was studied using water contact angle measurements, water/alcohol, and oil repellency tests, X‐ray photoelectron spectroscopy, and scanning electron microscopy. A design of experiments for different processing conditions was used. Plasma assisted‐graft polymerization of fluorocarbon in presence of the crosslinker di(ethyleneglycol) diacrylate (10:1 molar ratio of monomer/crosslinker) resulted in a polyfluorocarbon nanolayer on cotton, which was hydrophobic and durable to five home launderings. Abstract : High‐density, non‐thermal, glow discharge atmospheric plasma reactor was used for graft polymerization of the vapor deposited fluorocarbon C6 monomer. Monomer vapor was deposited, followed by static and dynamic plasma treatments to initiate and complete graft polymerization. Nanolayer fluorocarbon coating in presence of a crosslinker onto cotton is achieved that is water, alcohol, and oil repellent and durable to home launderings.